2015
DOI: 10.1159/000440703
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Model for Surgical Site Infection in the Gastric Cancer Surgery Using Data of 790 Patients

Abstract: Background: Understanding risk factors of surgical site infections (SSIs) in gastrectomy is important to provide the best treatment for the patients with gastric cancer. Methods: This is a retrospective observational study using the medical records of 790 patients with gastrectomy from 2005 through 2009. SSIs were classified into incisional SSIs (iSSIs) and organ/space SSIs (o/sSSIs). Results: iSSIs and o/sSSIs were detected in 41 (5.2%) patients and 68 (8.6%) patients, respectively. Open surgery was the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…Several studies have reported risk factors for SSIs after gastrectomy, including male sex, chronic liver disease, longer surgical time, advanced age, a BMI of 25 kg/m 2 or higher, diabetes mellitus, blood loss, TG, and combined resection procedures. [ 6 , 7 , 9 , 10 , 19 ] Similarly, male sex and TG were also risk factors in our study. However, other factors did not show a statistically significant difference.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Several studies have reported risk factors for SSIs after gastrectomy, including male sex, chronic liver disease, longer surgical time, advanced age, a BMI of 25 kg/m 2 or higher, diabetes mellitus, blood loss, TG, and combined resection procedures. [ 6 , 7 , 9 , 10 , 19 ] Similarly, male sex and TG were also risk factors in our study. However, other factors did not show a statistically significant difference.…”
Section: Discussionsupporting
confidence: 76%
“…To date, the overall incidence of SSIs is about 10% to 20%, and infections account for nearly half of the causes of death after major abdominal surgery. [ 6 , 7 , 11 14 ] It is crucially important to determine all the SSI risk factors, especially those factors that are modifiable so that SSIs can be prevented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue among physicians and surgical team members reportedly contributes to SSIs [ 34 ]. However, operative duration ≥ the T time was a risk factor for OS-SSI in the first study period and both SI-SSI and OS-SSI in the second study period, with varying mean operative durations.…”
Section: Discussionmentioning
confidence: 99%
“…Operative duration ≥ the T time is considered to reflect the surgeon’s skills and/or complexity of the surgery [ 34 ]. For example, gastrectomy is the most common gastrointestinal surgical procedure in Japan because of the high incidence of gastric cancer [ 35 ].…”
Section: Discussionmentioning
confidence: 99%